Observation of the electric Breit–Rabi effect - Shao-Zheng Wang; Shou-Bo Wang; Zhi-Jin Tao; Tian Xia; Zheng-Tian Lu (Proceedings of the National Academy of Sciences, 2025)
The response of an atom to external electric and magnetic fields can reveal fundamental atomic properties. It has long been verified that, in a static magnetic field, those atomic energy levels with hyperfine interactions shift according to the Breit–Rabi formula, which introduces nonlinear dependence on the magnetic field. On the other hand, the corresponding Breit–Rabi dependence on a static electric field has not been observed before due to a combination of experimental challenges. Here, we precisely measure the Stark shift of the 6 s 2 1 S 0 ↔ 6 s 6 p 1 P 1 transition of 171 Yb ( I = 1/2) with cold atoms held by an optical dipole trap in a static electric field up to 120 kV/cm. We observe the electric Breit–Rabi effect displaying high-order ( E 4 and E 6 ) DC Stark shifts. These effects arise from the influence of the strong electric field on hyperfine interactions.